Higher Education Marketing: A Study of the Contribution of Marketing and Branding Strategies to Interest in Entering Islamic Higher Education - Abdul Haris Abdullah; Shinta Nento (IAIN Manado, 2024)
Higher Education Marketing: A Study of the Contribution of Marketing and Branding Strategies to Interest in Entering Islamic Higher Education. This study aims to determine the effect of higher education marketing and branding strategies on interest in entering Islamic universities. The object of this research is students who come from two state Islamic universities. This study uses a quantitative approach with 124 respondents, sampling using random sampling technique, and a questionnaire as a measuring tool. Data analysis used the Structural Equation Modeling (SEM) method, and to test the suitability of the model in the study with the help of the SmartPLS version 3.2 application. The results of this study conclude that higher education marketing and branding strategies affect the interest in entering higher education